2014
DOI: 10.1038/emi.2014.58
|View full text |Cite
|
Sign up to set email alerts
|

The vaccine potential of Bordetella pertussis biofilm-derived membrane proteins

Abstract: Pertussis is an infectious respiratory disease of humans caused by the gram-negative pathogen Bordetella pertussis. The use of acellular pertussis vaccines (aPs) which induce immunity of relative short duration and the emergence of vaccine-adapted strains are thought to have contributed to the recent resurgence of pertussis in industrialized countries despite high vaccination coverage. Current pertussis vaccines consist of antigens derived from planktonic bacterial cultures. However, recent studies have shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 57 publications
(75 reference statements)
9
60
2
1
Order By: Relevance
“…BipA is a biofilm‐derived protein that is thought to be involved in transmission and/or adhesion . Deletion of BipA in Bordetella bronchiseptica and B. pertussis showed no significant difference in colonization ability, however BipA can be highly immunogenic . Downregulation of BipA may allow current B. pertussis strains to hide from immune recognition without affecting colonization ability.…”
Section: Discussionmentioning
confidence: 99%
“…BipA is a biofilm‐derived protein that is thought to be involved in transmission and/or adhesion . Deletion of BipA in Bordetella bronchiseptica and B. pertussis showed no significant difference in colonization ability, however BipA can be highly immunogenic . Downregulation of BipA may allow current B. pertussis strains to hide from immune recognition without affecting colonization ability.…”
Section: Discussionmentioning
confidence: 99%
“…Complement evasion molecules fulfill most, if not all, of these criteria. Studies show immunogenicity of multiple complement evasion molecules in vaccination models including B. pertussis Vag8, S. pneumoniae PspC and S. aureus SdrE (Stranger-Jones et al, 2006; Ferreira et al, 2009; de Gouw et al, 2014). Furthermore, the vast majority of the complement evasion molecules described in this review are expressed by most, if not all, virulent strains of one particular bacterial species and the proteins are highly conserved (Bhattacharjee et al, 2013; Fleury et al, 2014; de Gouw et al, 2014; Hallström et al, 2015).…”
Section: Complement Evasion Molecules As Vaccine Targetsmentioning
confidence: 99%
“…Ongoing studies support the concept that B. pertussis forms biofilm during infection; recent clinical isolates form more biofilm compared to a lab‐passaged isolate, BP338, and de Gouw et al . showed that biofilm‐derived antigens protect mice from B. pertussis infection (de Gouw et al ., ; Arnal et al ., ). The closely related animal pathogen, B. bronchiseptica forms biofilm in vitro on abiotic surfaces and biofilm formation contributes to its chronic infection of dogs and other mammals (Fenwick, ).…”
Section: Introductionmentioning
confidence: 99%